A notícia entre jornalismo e comunicação estratégica: reflexões teórico-metodológicas - SAMPAIO, Claudiane de Oliveira Carvalho (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
This article proposes to present theoretical-methodological notes for the analysis of the news built on the relationship between journalism and strategic communication. Discourse Analysis (AD) of socio-discursive, hermeneutic (H) and communication theories is articulated in order to encompass the established communicative contracts, the construction of the effect of a sense of truth, the criteria and values mobilized. In this direction, the article is composed of three parts. At first, the news is presented as discourse, a narrative fabric that articulates “to make known” and “to make seduce” (Charaudeau, 2012). The second part is dedicated to the construction of news that takes place on the border, at the intersections between journalism and strategic communication. Finally, there is a brief survey of challenges and perspectives instituted in the contemporaneity of the news construction in focus. The text understands the news as a socio-discursive production, crossed by the actors in the scene, purpose and purpose of the communicative contract and communicational ambience.